The Effect of Moringa (Moringa oleifera) Leaf Juice on Blood Sugar Levels in Type II Diabetes Mellitus Outpatients at Babah Buloh Public Health Center, North Aceh District - Zuhra, Nabila; Junita, Dini (Jurusan Gizi, Poltekkes Kemenkes Aceh, 2025)
Diabetes mellitus is characterized by elevated blood glucose levels that exceed the normal range. In addition to pharmacological treatment, blood sugar levels in individuals with diabetes can also be managed using herbal therapies. One such alternative is Moringa (Moringa oleifera) leaf juice, which contains various bioactive compounds such as flavonoids, beta-carotene, thiamine, riboflavin, vitamin C, calcium, and zinc—many of which possess antidiabetic properties and are believed to be effective in lowering blood glucose levels. This study aimed to determine the effect of Moringa leaf juice on blood sugar levels among type II diabetes mellitus outpatients in the working area of Babah Buloh Public Health Center, North Aceh District. A quasi-experimental study was conducted using a pretest–posttest control group design from December 7 to 14, 2024. The intervention lasted for seven consecutive days, during which blood glucose levels were measured using the Easy Touch glucometer. Data were analyzed using paired t-tests and independent t-tests. The results showed that in the intervention group, the average blood sugar level decreased from 182.1 mg/dL to 166.3 mg/dL, with a mean reduction of 15.7 mg/dL. In the control group, levels decreased from 177.8 mg/dL to 170.5 mg/dL, with a mean reduction of 6.7 mg/dL. These findings indicate that Moringa leaf juice had a significant effect on reducing blood sugar levels in type II diabetes mellitus patients in the Babah Buloh Health Center working area in 2024. It is recommended that Moringa leaf juice be considered as a complementary therapy for managing blood glucose levels in diabetic patients.